Korotkoff sounds dynamically reflect changes in cardiac function based on deep learning methods - Lin, Wenting; Jia, Sixiang; Chen, Yiwen; Shi, Hanning; Zhao, Jianqiang; Li, Zhe; Wu, Yiteng; Jiang, Hangpan; Zhang, Qi; Wang, Wei; Chen, Yayu; Feng, Chao; et al. (Frontiers in Cardiovascular Medicine, 2022)
Korotkoff sounds (K-sounds) has been around for over 100 years and is considered the gold standard for blood pressure (BP) measurement. K-sounds is also unique for diagnosis and treatment of cardiovascular diseases, however, its efficacy is limited. Heart failure (HF) incidences are increasing, which necessitates the development of a rapid and convenient pre-hospital screening method. In this review, we propose a deep learning (DL) method and the possibility of using K-methods to predict cardiac function changes for detection of cardiac dysfunctions.